(untitled) (Ustozlar uchun, 2026)
This paper examines the revival of interest in the storytelling method as an effective pedagogical approach in modern education. It highlights the role of storytelling in enhancing students’ engagement, motivation, and communication skills. The study analyzes both traditional and digital forms of storytelling and their impact on learning outcomes. The findings suggest that storytelling supports interactive, learner-centered education and contributes to the development of critical thinking and creativity.